Pregnancy and menstrual hormone levels in mothers of twins compared to mothers of singletons. - Thomas, H; Murphy, M; Key, T; Fentiman, I; Allen, D; Kinlen, L (1998)
This study examined the hormonal differences between premenopausal mothers of twins and other premenopausal parous women during and after pregnancy. Serum concentrations of oestradiol and testosterone between 6 and 20 weeks of gestation were measured for 11 mothers of twins and 115 mothers of singletons selected from the controls in a case-control study of cryptorchidism. Serum concentrations of oestradiol, progesterone, testosterone, follicle stimulating hormone and sex hormone-binding globulin during the menstrual cycle were measured for 25 mothers of twins and 38 mothers of singletons recruited as a part of a prospective study of breast cancer risk. During pregnancy, women carrying twins had a 58% higher geometric mean oestradiol concentration (p = 0.02) and a 50% higher testosterone concentration (p = 0.03) than women carrying singletons. Women who had previously had twins demonstrated a 49% higher mean concentration of follicle stimulating hormone (p = 0.02) and a 42% higher concentration of sex hormone-binding globulin (p = 0.03) than women who had singletons only, but no significant differences in oestradiol, progesterone and testosterone concentrations. The increased concentrations of follicle stimulating hormone during the menstrual cycle of mothers of twins, which has also been reported in two previous studies suggests that follicle stimulating hormone level may be an important determinant of dizygotic twinning.